2010
DOI: 10.1182/blood-2009-06-228684
|View full text |Cite
|
Sign up to set email alerts
|

Malignant cells fuel tumor growth by educating infiltrating leukocytes to produce the mitogen Gas6

Abstract: The transforming and tumor growthpromoting properties of Axl, a member of the Tyro3, Axl, and Mer (TAM) family of receptor tyrosine kinases (TAMRs), are well recognized. In contrast, little is known about the role of the TAMR ligand growth arrest-specific gene 6 (Gas6) in tumor biology. By using Gas6-deficient (Gas6 ؊/؊ ) mice, we show that bone marrow-derived Gas6 promotes growth and metastasis in different experimental cancer models, including one resistant to vascular endothelial growth factor inhibitors. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
147
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 148 publications
(162 citation statements)
references
References 67 publications
(117 reference statements)
14
147
1
Order By: Relevance
“…As Axl mAbs do not seem to have a significant effect on the expression of Axl on TAMs, but downregulate receptor expression on tumor cells, it is likely that anti-Axl mAbs modulate cytokine/ chemokine secretion from TAMs by blocking the crosstalk between tumor and stromal cells. These results are consistent with the recent reports that tumor cells could promote their growth by educating infiltrating leukocytes to induce the expression of Gas6 (Loges et al, 2010); and a small-molecule inhibitor of Axl reduced the expression of granulocyte macrophage colony-stimulating factor in 4T1 breast tumor cells (Holland et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…As Axl mAbs do not seem to have a significant effect on the expression of Axl on TAMs, but downregulate receptor expression on tumor cells, it is likely that anti-Axl mAbs modulate cytokine/ chemokine secretion from TAMs by blocking the crosstalk between tumor and stromal cells. These results are consistent with the recent reports that tumor cells could promote their growth by educating infiltrating leukocytes to induce the expression of Gas6 (Loges et al, 2010); and a small-molecule inhibitor of Axl reduced the expression of granulocyte macrophage colony-stimulating factor in 4T1 breast tumor cells (Holland et al, 2010).…”
Section: Discussionsupporting
confidence: 92%
“…The ccRCC cell lines examined in our study expressed low to high levels of endogenous GAS6. Infiltrating immune cells including leukocytes also have the capacity to produce GAS6 and stimulate TAM receptor signaling on tumor cells (41). Thus, both autocrine and paracrine production of GAS6 may contribute to SRC activation in kidney cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that both tumor-and stromalderived GAS6 contributes to tumor growth and metastasis. Loges et al used GAS6-deficient mice to demonstrate that bone marrow-derived GAS6 promotes the growth and metastasis of a variety of cancer cell lines deficient for endogenous GAS6 (41). In these models, the tumor microenvironment stimulated the upregulation of GAS6 in leukocytes, which in turn mediate the growth and metastasis of GAS6-deficient tumor cells.…”
Section: Discussionmentioning
confidence: 99%
“…tumor necrosis factor, TNF; reactive oxygen species, ROS) appears to support neoplastic transformation [6], whereas in established cancers the expression of M2-like phenotypes with immunosuppressive, pro-angiogenic and tissue remodelling activities promotes immune escape, tumor growth and malignancy [1,6,[52][53][54][55]. Recent addition to the molecular repertoire of TAMs includes semaphorin 4D (Sema4D) [56] and growth arrest-specific 6 (Gas6) [57], which are respectively involved in promoting tumor angiogenesis and cancer cell proliferation. Of note, Src homology 2-containing inositol-5′-phosphatase-1 (SHIP1)-deficient mice, which exhibit a spontaneous macrophage drift towards M2 polarization, display increased growth of transplanted tumors [58].…”
Section: Tamcs Functionsmentioning
confidence: 99%